2020
DOI: 10.3390/met10030367
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Impact Mitigation of the Iron Ore Direct Reduction Process through Computer-Aided Optimization and Design Changes

Abstract: The steel industry is known to have one of the highest environmental impacts on the industrial sector, especially in terms of CO2 emissions. The so-called direct reduction route, which makes use of reformed natural gas along with top gas recycling to reduce iron oxide pellets with H2 and CO, is responsible for lower CO2 emissions than the classic blast furnace route and is currently under development. The present article focuses on the direct reduction process and discusses means to further decrease the CO2 em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Subsequently, Bechara et al [ 93 ] performed optimization to improve the DR plant performance in terms of CO 2 emissions. Like their previous work, they used a custom model in Aspen plus and modeled the DR plant operation, but this time they used a computer‐aided multivariable process optimization procedure offered in Aspen Plus instead of the simple manual optimization.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, Bechara et al [ 93 ] performed optimization to improve the DR plant performance in terms of CO 2 emissions. Like their previous work, they used a custom model in Aspen plus and modeled the DR plant operation, but this time they used a computer‐aided multivariable process optimization procedure offered in Aspen Plus instead of the simple manual optimization.…”
Section: Discussionmentioning
confidence: 99%
“…The outlet gas (syngas) consists of 51 mol.-% H2, 35 mol.-% CO, 8 mol.-% H2O, 1 mol.-% CH4 and 5 mol.-% CO2, which is in good agreement with literature values. 14,[29][30][31] The firebox operates with an excess air of 15% and maintains a thermodynamic temperature of greater than 1000 °C in the reforming section to facilitate the endothermic reforming reactions. To maximize the efficiency of the firebox, the combustion air is pre-heated to 500 °C against the flue gas before it enters the stack.…”
Section: Ch + H O → 3h + Comentioning
confidence: 99%
“…Higher excess ratios increase the chemical potential/driving force for the chemical reactions inside the shaft furnace; however, this increases the recycle stream and work associated with recompression. Typical top gas concentrations of the shaft furnace range from 33-49 mol.-% for H2, and 19-26 mol.-% for CO. [29][30][31] The temperature of the top gas leaving the shaft furnace ranges from 300-450 °C. 29,30,33 Thereafter, the top gas is quenched in a water scrubber to remove water produced by the iron ore reduction process as well as dust, and to lower the gas temperature for the recycle compressor.…”
Section: Dri Shaft Furnacementioning
confidence: 99%
See 1 more Smart Citation
“…By conducting different simulations with different inlet gas compositions, they found that NG consumption and CO 2 emissions could be reduced by the setting of ratios H 2 /CO and (H 2 + CO)/(H 2 O + CO 2 ) at 1.23 and 12, respectively [23]. The same authors solved an optimization problem aiming to identify the values of a DR-NG-based process operating parameters to minimize the emissions generated [24]. Sarkar et al developed a DR-NG shaft thermochemical model to estimate the energy requirement and predict the emissions due to crude steel production, adopting an EAF.…”
Section: Literature Review Of Direct Reduction Iron Processesmentioning
confidence: 99%